South Africa's headquarter company regime: a gateway barred from within - Mukumba, Tsangadzaome A (Department of Commercial Law, 2017)
This paper aims to determine whether South Africa's section 9I headquarter company regime is fit for the purpose of incentivising multi-national enterprises to locate strategically beneficial activities in South Africa. Part I investigates the tax policy appropriateness of s9I in the context of a developing, but regionally dominant South Africa. It finds that the passive intermediary holding company activities in fact incentivised by s9I are not directly beneficial to South Africa. While the active functions associated with true headquarter companies would produce the positive externalities needed by South Africa. Given the regional competition in this arena and strategic advantages in South Africa Part I advocates the incentivisation of regional headquarter companies, specifically regional treasury companies, as the most appropriate policy choice. Part II interprets the provisions of s9I regime to determine their effect on its commercial attractiveness. The analysis covers both the interpretation of the relevant provisions under South African tax law and the place of s9I in the broader legal atmosphere. It is determined that due to an overemphasis on restricting the activities of prospective s9I companies and preventing the erosion of the tax base, the provisions of the regime themselves undermine its commercial attractiveness. The ultimate conclusion reached here is that although South Africa is indeed poised to be the natural gateway into Africa, the s9I regime is both inappropriately designed and unattractive to prospective multi-nationals looking to enter the region. Therefore, if the regime adopts the 'effective, reliable tax relief for strategic local substance' model of incentivisation South Africa can still reap the benefits of direct investment by MNEs.